Determinación del tiempo del tiempo del estacionamiento temporal en las bahias de Bogotá (2013)
The present work of degree determines the time of permanence of the vehicles that at the moment are using the bays enabled for the temporary parking in the city of Bogota DC, by means of the development of a parking study by means of the registry of plates, that consists of registering the last four digits of the license plates of the vehicles that enter and leave the parking bays manually and the hour and minute that this event occurs, where the surveyor walks along the sidewalks, in a circular direction, by the end of the cycle again through the initial bay, in five areas of the city; taking into account information on land uses, supply of bays and vehicular demand. This study is carried out because the current regulations do not define the minimum or maximum time where the users of these spaces can park, nor the competent authorities have the knowledge to be able to regulate and control this parking in the city of Bogotá D.C.